Speech rate as a measure of short-term variation in depression. - Teasdale, J; Fogarty, S; Williams, J (1980)
Experimental investigation of the state of depression is at present hindered by the lack of simple, objective, repeatable measures of components of the state. Covariation between self-report measures of affect and simple measure of speech rate was investigated in a series of studies of both clinical and normal subjects, using single-case and group designs. Slowing of speech was significantly and substantially correlated with self-reports of increased unpleasant affect in certain situations. This suggests that the speech measure may usefully reflect a behavioural component of a state of retarded-type depression.